Severe Acute Colitis: A Countdown Diagnostic Challenge - Nacir, Oussama; Riyad, Abbas; Errami, Adil Ait; Oubaha, Sofia; Samlani, Zouhour; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
Introduction: Severe acute colitis (SAC) complicates 10-15% of ulcerative colitis and more rarely Crohn's disease or infectious colitis [1]. It is a medical and surgical emergency requiring rapid diagnosis and early management. It can lead to major digestive mutilation, which can cause sequelae that often alter the quality of life of patients for decades [2]. In this study, spread over 10 years, we propose a descriptive analysis of the epidemiological, clinico-paraclinical and evolutionary aspects of a series of cases of SAC admitted to the Mohammed VI University Hospital of Marrakech. We will then review the diagnostic procedures that preceded, but did not prevent, recourse to surgery, discussing them in the light of the current literature. Materials and Methods: This is a retrospective observational study with a descriptive and analytical aim, spread over 10 years, from January 2011 to December 2020, including all patients admitted to the Mohammed VI University Hospital of Marrakech and operated on for acute severe colitis and whose diagnosis was retained on the basis of a set of arguments. An exploitation form was chosen as a means of investigation. Data collection was based on hospitalization registers, patients' medical records, the "Hosix" computerized system, and the collaboration of the medical and paramedical staff of the department and the operating room. Statistical analysis was performed using SPSS version 19.0 software. Results: Out of a total of 550 inflammatory bowel disease (IBD) cases admitted to the Mohammed VI University Hospital of Marrakech, 100 patients (18.2%) presented with severe acute colitis during the period of our study. The operated SACs meeting the inclusion criteria of our study represented 20% (20 cases) of the total number of targeted SACs. The mean age of the patients was 34 years. The age group between 20 and 40 years represented 65% of the cases with a sex ratio of 0.81. The SAC was inaugural in 7 patients (35%) and had complicated a known inflammatory bowel disease in 13 patients (65%). The clinical picture consisted of bloody glutinous emissions and abdominal pain in 100% of cases. Abdominal examination on admission revealed abdominal sensitivity in 85% of cases, and tenderness in 15% of cases. The Blood count was normal in 25% of cases with an average hemoglobin of 12 g/dl. the c-reactive protein was elevated in 85% of patients (17 cases) with an average of 120 mg/l. Hypoalbuminemia was noted in 17 patients (85%). The unprepared abdominal X-ray (UAP), performed in 80% of the patients, was normal in 60% of the cases, with pneumoperitoneum in 10% and colectasis in 10%. Abdominal ultrasound was performed in 95% of the patients and revealed digestive thickening in 75% of the cases and a medium-sized peritoneal effusion in 30% of the cases. Abdominal CT scan was performed in 75% (15 patients), confirmed digestive thickening in 73% of cases, a medium-sized effusion in 33% of cases, pericolic fat infiltration in 33% of cases, right iliac fossa abscess (6%) and colectasis in two cases (12%). Left colonoscopy was performed in 18 patients (96%). Endoscopic signs of severity were found in 77% of patients. The diagnosis of severe acute colitis was made on the basis of the criteria of Truelove and Witts. In terms of therapeutic management, rest of the digestive tract with parenteral nutrition was indicated in 7 patients (35%). Antibiotic treatment was initiated in 65% of cases. The first-line medical treatment of SAC consisted of intravenous corticosteroid therapy in 16 patients (85%). Local treatment with mesalazine or salazopyrin was used in 65% of cases (13 patients). Failure of first-line medical treatment in 9 patients (45%) led to emergency colectomy, and 6 non-operated patients were put on cyclosporine. Six patients underwent colectomy for failure of second-line treatment. In contrast, two patients were treated with third-line infliximab with poor clinical tolerance which also led to colectomy. At 2 years after colectomy, 3 of our patients (15%) had recurrence on the remaining rectal stump. The functional outcome was marked by an average of 2 to 3 daytime bowel movements, and 0 to 1 nighttime bowel movement in most patients, only one case of rectal imperiousness (5%) and no case of sexual disorders or infertility. Conclusion: Acute severe colitis is a alarming complication of chronic inflammatory bowel disease. Its management must be rapid, reasoned and coordinated from the outset, based on multidisciplinary collaboration. Our study focuses on the initial diagnostic and therapeutic difficulties of GAC, which always constitute a challenge in reverse count.